Herbicide and fertilizer compatibility under normal and stale seedbed sowing of wheat (Triticum aestivum) at different levels of nitrogen - Yadav, P K; Kurchania, S P; Tiwari, J P (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during the winter season of 1988-89 and 1989-90 to study herbicide and fertilizer compatibility forweed control in wheat (Triticum aestivum L. emend. Fiori & Paol.) under different levels of nitrogen and methods of seedbed preparation. Four methods of isoproturon (1.0 kg/ha) application were spray pre-emergence, post-emergence, broadcast as mixture with superphosphate basal at pre-emergence stage and with urea topÂ·dressed at post-emergence stage; and 3 levels of N were 60, 90 and 120 kg/ha. Isoproturon @ 1.0 kg/ha as pre-emergence spray effectively controlled small canarygrass (Phalaris minor Retz.) and annual broad-leaf weeds, viz scarlet pimpernel (Anagallis arvensis L.), lambsquarters (Chenopodium album L.), toothed medick (Medicago hispida Gaertn.), sweet clover (Melilotus alba Medikus), common purslane (Portulaca oleracea L.) and corn spurry (Spergula arvensis L.). It showed weed-control efficiency 64%, followed by isoprouron post-emergence spray (57%), isoproturon +urea top-dressed (49%) and isoproturon + superphosphate ( 41 %). The weed-control efficiency increased under stale seedbed (34%) compared with normal seedbed. An increase in N level (60-120 kg/ha) also increased the weed-control efficiency (11-21 %) and reduced the weed biomass (11-21 %). The grain yield (4 270 kg/ha) and net profit (Rs 7 369) were higher under stale seedbed and with increase in N level. The mean yield under different isoproturon treatments (4252-4321 kg/ha) was at par with that under hand-weeding (4 222 kg/ha) but significantly superior to weedy control (3 667 kg/ha), and hence proved economical. The benefit: cost ratio with isoproturon was higher (2.53-2.58) than that with hand-weeding (2.19) and weedy control (2.44).